2007
DOI: 10.1152/ajpcell.00101.2007
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of voltage-gated K+ channels in mouse pulmonary artery smooth muscle cells

Abstract: June 20, 2007; doi:10.1152/ajpcell.00101.2007.-Mice are useful animal models to study pathogenic mechanisms involved in pulmonary vascular disease. Altered expression and function of voltage-gated K ϩ (KV) channels in pulmonary artery smooth muscle cells (PASMCs) have been implicated in the development of pulmonary arterial hypertension. KV currents (IK(V)) in mouse PASMCs have not been comprehensively characterized. The main focus of this study was to determine the biophysical and pharmacological properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
(65 reference statements)
4
8
0
Order By: Relevance
“…This demonstrates the contribution of K V channels but not BK Ca channels to this outward current. Similar observations were recently reported in adult mice of a different strain (23). Western blotting analysis of K V 1.5 ␣-subunit and BK Ca ␣-subunit expression showed that both proteins were present in the main PA of adult mice born in normoxia, suggesting that, in basal conditions, K Ca channels are present but not active.…”
Section: Discussionsupporting
confidence: 88%
“…This demonstrates the contribution of K V channels but not BK Ca channels to this outward current. Similar observations were recently reported in adult mice of a different strain (23). Western blotting analysis of K V 1.5 ␣-subunit and BK Ca ␣-subunit expression showed that both proteins were present in the main PA of adult mice born in normoxia, suggesting that, in basal conditions, K Ca channels are present but not active.…”
Section: Discussionsupporting
confidence: 88%
“…The biophysical features of this current are consistent with previously reported voltage-gated, Ca 2ϩ -independent K ϩ currents with rapid rates of activation and steady-state inactivation in pulmonary smooth muscle (32). The rapid rate of activation of I KH was comparable to observations made in rabbit portal vein smooth muscle (time to peak ϳ20 ms) (4) but slower than the ultrafast activating Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Freshly dissociated PASMC from mouse PA isolated from second-to third-order intrapulmonary arterial branches (100-to 400-m diameters) were used to measure the electrophysiological properties of VDCC. As previously reported (28), the freshly dissociated mouse PASMC from intrapulmonary arteries were oblong, unlike the long spindle-shaped cells isolated from other species ( Fig. 2A).…”
Section: Functional Role Of Vdcc In Pulmonary Vasoconstrictionsupporting
confidence: 78%